Development of Problem-Based Learning Integrated Sasambo Ethnochemistry in Colloid-Based Chemistry Teaching Materials - Andayani, Yayuk; Mutiah, Mutiah; Purwoko, Agus Abhi; Sofia, Baiq Fara Dwirani; Hidayanti, Ermia (Jurnal Pijar Mipa, 2024)
This research aims to determine the feasibility of product development for colloid-based chemistry teaching materials and problem-based learning integrated with Sasambo ethnochemistry to increase students' chemical literacy. This research is part of a development research procedure that adopts the 4-D model, with stages to define, design, develop, and disseminate. Test the suitability of teaching materials using a questionnaire to test content validity and construct validity. And reliability. The content and construct validity analysis technique uses the V index, while the reliability of teaching materials uses the kappa moment coefficient (K). The content and construct validity analysis results showed that the criteria were very valid, with a V index of 91.36% and 90.7%. The reliability analysis results of teaching materials obtained a kappa moment coefficient (K) of 0.88 with a very high reliability category. Based on the validity and reliability values, it is concluded that colloid-based chemistry teaching materials and problem-based learning Sasambo's integrated ethnochemistry are very suitable for learning.